THE OBJECTIVE NECESSITY OF THE METHOD OF MICROCHIP-BASED ACCOUNTING OF SERVICE DOGS IN THE FIELD OF CYNOLOGY (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In this article, the development of the field of cynology in the Republic of Uzbekistan and the creation of modern advanced technologies - methods of keeping records of service dogs - microchip and its relevance, objective necessity are presented. Also, the importance of this methodology, scientific proposals and practical recommendations for the training of service dogs and digitalization of educational and training processes in the future are outlined.